Surface-tension-driven coalescence - Thompson, Alice B. (2012)
When fluid droplets coalesce, the flow is initially controlled by a balance between surface tension and viscosity. For low viscosity fluids such as water, the viscous lengthscale is quickly reached, yielding a new balance between surface tension and inertia. Numerical and asymptotic calculations have shown that there is no simply connected solution for the coalescence of inviscid fluid drops surrounded by a void, as large amplitude capillary waves cause the free surface to pinch off. We analyse in detail a linearised version of this free boundary problem.